2023
DOI: 10.1590/1517-7076-rmat-2023-0241
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on granite waste and alccofine in concrete

Sakthivel Rajendran,
Ramadevi Kanagaraj

Abstract: Population growth and rapid pace of globalization have increased the demand for construction materials. River sand is one of the main materials used to make the fine aggregate for concrete. As a result, finding an alternative to sand has become crucial. Granite debris and M sand are employed in place of river sand in this experiment. In this experiment, granite debris as well as M sand are used in place for river sand. Concrete constructed using granite waste and alccofine was compared to ordinary concrete tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Given the importance of finding a better destination for granite and marble waste, other research can also be found, such as applications in red ceramics [11], in materials and concrete structure [12,13], in lightweight aggregates for concrete [14], among others.…”
Section: Introduction 1general Introductionmentioning
confidence: 99%
“…Given the importance of finding a better destination for granite and marble waste, other research can also be found, such as applications in red ceramics [11], in materials and concrete structure [12,13], in lightweight aggregates for concrete [14], among others.…”
Section: Introduction 1general Introductionmentioning
confidence: 99%